IMPLEMENTASI METODE HAFALAN PADA MATA PELAJARAN PAI SURAH AL-ANBIYA' AYAT 30 DAN SURAH AL-A'RAF AYAT 54 UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS VII A DI SMPS IT SULTHONIYAH SAMBAS - Nur Fitri; Rusiadi; Muspian (CV. Adiba Aisha Amira, 2026)
This study aims to describe the implementation of the memorization method (hafalan) in Islamic Religious Education (PAI) on Surah Al-Anbiya' verse 30 and Surah Al-A'raf verse 54 to improve the learning motivation of seventh-grade students at SMPS IT Sulthoniyah Sambas in the 2025-2026 academic year. The study focuses on three aspects: (1) planning, (2) implementation, and (3) evaluation of the memorization method. A qualitative descriptive approach was employed. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing. Source triangulation and member check were used to validate the data. The findings reveal: (1) Teachers planned lessons by thoroughly preparing material, studying verse content, segmenting verses into smaller parts, and organizing talaqqi, repetition, and muraja'ah techniques; (2) Implementation was carried out through teacher active engagement, attendance checking, motivation delivery, triggering questions, and material explanation; (3) Evaluation used oral memorization tests that served not only as assessment but also as continuous guidance for students.